2016
DOI: 10.1002/acp.3250
|View full text |Cite
|
Sign up to set email alerts
|

Training Melanoma Detection in Photographs Using the Perceptual Expertise Training Approach

Abstract: SummaryAlthough a deadly form of skin cancer, melanoma is treatable if detected early. However, current rule‐based training practices in melanoma detection are not effective. We assessed an innovative technique to train melanoma detection using the perceptual expertise principles. Participants in the training group were trained to categorize melanoma and benign lesions to 95% accuracy. Participants in the control group received no training. Prior to testing all participants reviewed the ABCDE rules. Training w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…The novices tested in this study performed at chance level before training. This differed from previous studies in which participants were trained to identify bone fracture or skin melanoma (Chen et al, 2017;Xu et al, 2016). The pre-training performance in those studies was above chance, suggesting that the abnormalities were discernible even without training.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The novices tested in this study performed at chance level before training. This differed from previous studies in which participants were trained to identify bone fracture or skin melanoma (Chen et al, 2017;Xu et al, 2016). The pre-training performance in those studies was above chance, suggesting that the abnormalities were discernible even without training.…”
Section: Discussioncontrasting
confidence: 91%
“…Other fields emphasize the development of perceptual pattern templates that support the recognition of normal and abnormal images (van der Gijp et al, 2014). Perceptual learning can also complement conceptual knowledge, such as in the identification of melanoma (Xu, Rourke, Robinson, & Tanaka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Novices may develop perceptual expertise through experience or through targeted visual perception training (VPT). Previous work demonstrated that VPT successfully improved the ability of undergraduates to diagnose melanoma, although follow-up was limited to 1 week 5. This prospective cohort trial of preclinical medical students was performed to evaluate the effectiveness of a novel, technology-based VPT system for melanoma detection with retention assessed at 4 weeks.…”
mentioning
confidence: 99%
“…In basic and clinical studies in which feedback is used to visually train subjects, partial feedback 20-21 or detailed feedback 22-23 has never been used systematically. Our results suggest that training using partial feedback is sufficient for PL of calcifications.…”
Section: Discussionmentioning
confidence: 99%